MORPHOLOGY, MEDICINAL PROPERTIES AND INFLUENCE OF AGROCHEMICAL PROPERTIES OF LIGHT SEIROZEMS OF SOUTHERN FERGANA (Scientific journal of the Fergana State University, 2025)
The article studies the habitats and medicinal properties of the plant Capparis spinosa L. in the light gray soils of the South of Fergana, provides literary information about its role in modern medicine, its chemical composition: organic and inorganic substances, vitamins.